Respon Mahasiswa Terhadap Project Based Learning dengan Penugasan Video Tutorial Uji Statistik - Fitriani, Rita; Sarkity, Dios (Jurusan Tarbiyah dan Pendidikan, 2023)
Merdeka belajar curriculum in college encourages student-oriented learning. One of the student-oriented learning is the Project Based Learning (PjBL) model. PjBL is defined as a way of learning in which using the project becomes a learning medium to obtain the expected competencies. PjBL emphasizes student-centered learning to produce meaningful and useful products. This study aims to analyze the response of students of Chemistry Education Study Program FKIP UMRAH in the implementation of PjBL by being assigned to make a statistical test tutorial video in the Educational Statistics course. A qualitative descriptive approach is the method in this study. The research subjects were all students of Chemistry Education S1 FKIP UMRAH semester III who took the Educational Statistics course. The research data collection technique was the distribution of student response questionnaires which was carried out after the PjBL was implemented. The research instrument is a questionnaire. The result of the research was that the implementation of PjBL with the assignment of video tutorials for statistical tests in the Education Statistics course received very good responses from students.